THE DISTINCTIONS BETWEEN ENGLISH AND FRENCH INFINITIVES - Mehriddinova Dilnoza Jamoliddin qizi; Kayumova Feruza Ruzimurad qizi; Ruziyeva Nasiba Kenjaevna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article explores the nuanced disparities between English and French infinitives, emphasizing key distinctions in structure, subject pronoun usage, negative constructions, and the incorporation of infinitive clauses. By dissecting these differences, the reader gains a comprehensive understanding of how infinitives function in each language, facilitating a more informed approach to language learning and usage. The annotations highlight crucial points such as the flexibility of English infinitives with the use of "to," the one-word structure of French infinitives with -er, -ir, -re endings, and the distinct approaches to subject pronouns, negative constructions, and infinitive clauses in both languages.